Assessment of Mutations Associated With Genomic Variants of SARS-CoV-2: RT-qPCR as a Rapid and Affordable Tool to Monitoring Known Circulating Variants in Chile, 2021 - Angulo, Jenniffer; Martinez-Valdebenito, Constanza; Pardo-Roa, Catalina; Almonacid, Leonardo I.; Fuentes-Luppichini, Eugenia; Contreras, Ana Maria; Maldonado, Constanza; Le Corre, Nicole; Melo, Francisco; Medina, Rafael A.; Ferrés, Marcela (Frontiers in Medicine, 2022)
Since the first report of SARS-CoV-2 infection in humans, the virus has mutated to develop new viral variants with higher infection rates and more resistance to neutralization by antibodies elicited after natural SARS-CoV-2 infection or by vaccines. Therefore, rapid identification of viral variants circulating in the population is crucial for epidemiological assessment and efforts to contain the resurgence of the pandemic. Between January and November 2021, we performed a large variant RT-qPCR-based screening of mutations in the spike protein of 1851 SARS-CoV-2-positive samples derived from outpatients from the UC-Christus Health Network in Chile. In a portion of samples (n= 636), we validated our RT-qPCR-pipeline by WGS, obtaining a 99.2% concordance. Our results indicate that from January to March 2021 there was a dominance of non-identifiable variants by the RT-qPCR-based screening; however, throughout WGS we were able to identify the Lambda (C.37) variant of interest (VOI). From March to July, we observed the rapid emergence of mutations associated with the Gamma variant (P.1), which was quickly replaced by the appearance of a combination of samples harboring mutations associated with the Delta variant (B.1.617.2), which predominated until the end of the study. Our results highlight the applicability of cost-effective RT-qPCR-based screening of mutations associated with known variants of concern (VOC), VOI and variants under monitoring (VUM) of SARS-CoV-2, being a rapid and reliable tool that complements WGS-based surveillance.